The joy of implications, aka pure Horn formulas: Mainly a survey - Wild, Marcel (Theoretical computer science, 2017)
Pure Horn clauses have also been called (among others) functional dependencies, strong association rules, or simply implications. We survey the mathematical theory of implications with an emphasis on the progress made in the last 30 years.